PEMETAAN PERUBAHAN PENGGUNAAN LAHAN DI WILAYAH KABUPATEN TAKALAR TAHUN 1999 - 2019 MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Buraerah, Muhammad Fikruddin; Rasyidi, Emil Salim; Sandi, Reski (Jurnal Ilmiah Ecosystem, 2020)
The high population growth implied with increasing of various needs such as residentials, industries, health, education etc. Otherwise, increasing of various life needs causing alteration of city land purpose. This research aimed to determine the extent, describe and analyze land use changes in the areas of Takalar Regency with landsat satellite image interpretation. The study design as quantitative methods. Primary data used were obtained by downloading the maps of Landsat 5 TM, 7 ETM+, and 8 OLI images in the areas of Takalar Regency, the geometric correction, the image cropping and the interpretation. Research data are 3 map of landsat image that is year 1999, 2009 and 2019. The spatial data were analyzed using overlay process (union). The results showed that the settlement has a very significant change increased by 23,137 ha or 35.17%, while the use of forest land / mixed garden was reduced by 12,463 ha or 54.99%. This events is still continues until now. Therefore, it is contributing big impact on environment such as increasing city temperature, which is causing the decrease of Takalar Regency citizen comfortability. Therefore, sustainable development needed, for sustainable environment.